Critical Analysis of Khālistān Movement and its Impacts on India-Canada Relations - Ghulam Murtaza; Muhammad Tanveer Jamal; M. Saleem Kakar; Hamayun Khan, (ASIAN Journal of International Peace & Security (AJIPS), 2024)
This paper discerns the development of the jingoistic emotions among the Sikhs and inspects the elements which give birth to the Khālistān movement. The real motive of this movement is to get a separate homeland for the Sikh community in Indian Punjāb. Indian constitution highlights that all persons are equally entitled to freedom of conscience and the right to freely profess, practice and propagate religion. The government of India paid little heed to the Sikh sentiments which at least become the paramount cause of the emergence of militancy in Punjāb. The present study uses an analytical and descriptive approach. The main focus of this study on the emergence of the Khālistān movement and critically evaluate the impacts of clash on diplomatic ties of Canada and India on the backdrop of Khalistan movement. Moreover, the study also explores the current events fuelled the diplomatic tensions between India and Canada. Additionally, the study also suggests that how to resolve this particular issue for future relations between two countries.